La roue de l’Histoire : frontières et territoires monétaires dans le nord-est de la péninsule Ibérique et la vallée de l’Èbre avant 153 av. J.-C. - Francisco Burillo Mozota (Mélanges de la Casa de Velázquez, 2005)
This article analyses the emergence of coining in the north-east of the Iberian Peninsula and the Ebro valley and its development up to the fall of Segeda in the year 153 BC. The first mints to produce coinage were the Greek colonies of Emporion and Rhode. As the Second Punic War progressed, their drachmas were imitated by a number of Iberian oppida, hierarchical centres of the city-states from which the names of ethnic groups are derived. In 179 BC, under Gracchus, Roman penetration reached the present-day Rioja and the territorial scope of the coinage spread to Celtiberian lands. Denarii were minted with Iberian inscriptions and Roman weights to meet the fiscal needs of the conquerors. Ases and small bronze coins also made their appearance for small purchases. With the Roman advance into the Celtiberian heartland, new mints appeared, but there were oppida, for instance Termes, and territories like that of the Vaccaei, which never became part of the monetary system and yet possessed a political structure based on the city-state.